2019
DOI: 10.1002/iub.2170
|View full text |Cite
|
Sign up to set email alerts
|

GATA factors in pancreas development and disease

Abstract: There is an urgent need for the development of novel therapeutics options for diabetic patients given the high prevalence of diabetes worldwide and that, currently, there is no cure for this disease. The transplantation of pancreatic islets that contain insulin-producing cells is a promising therapeutic alternative, particularly for type 1 diabetes. However, the shortage of organ donors constitutes a major limitation for this approach; thus, developing alternative sources of insulin-producing cells is of criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…2f , bottom ). This is in agreement with previously reported GATA4 expression in the pancreatic progenitor state that is subsequently restricted to mature acinar cells during pancreatic maturation (Villamayor et al , 2020). Thus, our results give a mechanistic insight into how pancreatic identity is established and maintained through specific temporal suppression of Shh signaling.…”
Section: Mainsupporting
confidence: 94%
See 3 more Smart Citations
“…2f , bottom ). This is in agreement with previously reported GATA4 expression in the pancreatic progenitor state that is subsequently restricted to mature acinar cells during pancreatic maturation (Villamayor et al , 2020). Thus, our results give a mechanistic insight into how pancreatic identity is established and maintained through specific temporal suppression of Shh signaling.…”
Section: Mainsupporting
confidence: 94%
“…1 was highly stage-specific, showing dramatic upregulation at four-week and downregulation at six-week timepoint. Previous studies have shown that GATA4 is required for pancreatic cell fate maintenance during pancreas development (Villamayor et al , 2020) but not for pancreatic cell fate specification since the mice with pancreas-specific Gata4 deletion develop a pancreas (Xuan et al , 2012). Importantly, GATA4 is essential for maintenance of pancreatic progenitor cell fate by downregulation of Shh signaling (Xuan et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this stage, cell lineage allocation to the main pancreatic fates (endocrine, acinar, and ductal) begins ( Zhou et al, 2007 ; Pan and Wright, 2011 ). The tip domains will end up producing acinar progenitors, whilst the trunk will produce bipotent ones ( Figure 1 ) ( Zhou et al, 2007 ; Pan and Wright, 2011 ; Villamayor et al, 2020 ). After E16.5, expansion of the acinar tissue is mainly driven by acinar cell replication rather than de novo formation of acini.…”
Section: Transcription Factors Governing Pancreas Developmentmentioning
confidence: 99%